Strong user rights in fisheries: A case study of assessing the impacts - Ragnar Arnason; Birgir Runolfsson (University of Iceland, Institute of Economic Studies (IoES), 2022)
In previous research it was concluded that a transition to SURFs (strong user rights in fisheries) has several economic, environmental, and social impacts. In this paper, the problem of assessing the values of these impacts is considered. First, this kind of an assessment is considered in general terms. It is found that the values of the impacts depend in general on the empirical situation at hand. Therefore, a broad result that a transition to SURFs is either beneficial or detrimental does not seem to be available. Following this finding, it is attempted to evaluate empirically prominent impacts of installing SURFs in the Philippines Marine fisheries. Based on the available data and some simple bioeconomic modelling, it is concluded that the economic and biological impacts are mostly beneficial and their sum highly positive. Because of lack of data, the social impacts of SURFs could not be evaluated. It appears unlikely that they are detrimental enough to render a transition to SURFs inadvisable.
Keywords: Q20; Q22; Q28; D61; 330; Strong user rights in fisheries; SURFs; evaluating the impacts of SURFs; Philippine fisheries; fisheries management